Implementation of Accounting Information Systems in SME: A Systematic Literature Review - Mediaty, M.; Indrijawati, Aini; Palureng, Rezvita Zalsabilah; Surisman, S.; Hariana, H. (Golden Ratio of Finance Management, 2025)
This study aims to analyze the implementation of Accounting Information Systems (AIS) in Micro, Small, and Medium Enterprises (SMEs) in Indonesia using the Systematic Literature Review (SLR) approach. AIS is important in improving operational efficiency, transparency, and accuracy of MSME financial data, which ultimately supports strategic decision-making and business competitiveness. However, implementing AIS in SMEs faces various challenges, such as low financial literacy, limited access to technology, and difficulties in integrating new systems with existing business practices. This study identifies key factors in AIS implementation, including the type of system used, the role of stakeholders, perceived benefits, and integration of AIS with other systems. The results show that successful AIS implementation depends on understanding local needs, access to formal financing, and social support. With the growing digitalization, SMEs have an excellent opportunity to improve their performance through proper AIS adoption. The findings of this study are expected to serve as a strategic guide for the future development of SMEs.